Perlindungan Hukum Terhadap Korban Tindak Pidana yang Dilakukan oleh Orang dengan Gangguan Jiwa - Rachman, Novita Ayu Nafisa; Sembiring, Malemna Sura Anabertha; Nardiman; I Made Kanthika (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The cause of the weak legal protection of victims of criminal acts in Indonesia is that the laws and regulations governing it are still unclear. In this research, the author will discuss issues related to the legal protection of victims of criminal acts committed by people with mental disorders (ODGJ) and efforts that can be made by victims of criminal acts committed by ODGJ to obtain compensation. The normative research method used by the author in discussing the case in this thesis refers to written regulations, data collection is done through literature study as well as examining laws and cases related to the legal protection of victims of criminal acts committed by ODGJ. From the results of the research, it can be concluded that the legal protection of victims of criminal acts in the justice system must be pursued by the state as a form of responsibility for the formulation of criminal legislation. Legal protection of victims of crimes committed by ODGJ can be done with compensation in the form of restitution as an additional punishment to fulfill the rights of victims that have not been obtained. Criminal law policy is expected to be able to provide firmer rules regarding compensation that can be systematically applied in criminal law policy.